A report on the major farm practice in Robina Farms - Cebu - Libanan, Marisa C.; Ducducan, Teodoro C.; Almencion, Jorge B. (Tacloban City Agricultural and Rural Development, University of the Philippines College Tacloban, 1982)
This study describes the observed operations management of large scale poultry farms, Robina Farms I, II and III in Cebu.
Undergraduate thesis (Bachelor of Science in Animal Science)--University of the Philippines College Tacloban, Summer 1982.
Keywords: Poultry -- Farm management and production; Poultry breeding